Opportunities to improve eco-agriculture through transboundary governance in transfrontier conservation areas - Chitakira, M.; Nhamo, L.; Torquebiau, Emmanuel F.; Magidi, J.; Ferguson, W.; Mpandeli, S.; Mearns, K.; Mabhaudhi, Tafadzwanashe (MDPI, 2022)
Transfrontier Conservation Areas (TFCAs) are critical biodiversity areas for the conservation and sustainable use of biological and cultural resources while promoting regional peace, cooperation, and socio-economic development. Sustainable management of TFCAs is dependent on the availability of an eco-agriculture framework that promotes integrated management of conservation mosaics in terms of food production, environmental protection or the conservation of natural resources, and improved human livelihoods. As a developmental framework, eco-agriculture is significantly influenced by existing legal and governance structures at all levels; this study assessed the impact of existing legal and governance frameworks on eco-agriculture implementation in the Lubombo TFCA that cuts across the borders between Mozambique, Eswatini, and South Africa. The assessment used a mixed research method, including a document review, key informant interviews, and focus group discussions. Although the three countries have no eco-agriculture policies, biodiversity practices are directly or indirectly affected by some policies related to environmental protection, agriculture improvement, and rural development. The assessment found that South Africa has the most comprehensive policies related to eco-agriculture; Mozambican policies mainly focus on equity and involvement of disadvantaged social groups, while Eswatini is conspicuous for explicitly making it the responsibility of each citizen to protect and safeguard the environment. The protection of conservation areas is critical to preserving natural habitats and ensuring the continued provision of ecosystem services. The lack of transboundary governance structures results in the Lubombo TFCA existing as a treaty on paper, as there are no clear processes for transboundary cooperation and collaboration.